Sposób ukształtowania obligatoryjnych elementów skargi o stwierdzenie niezgodności z prawem prawomocnego orzeczenia a jego wpływ na skuteczność dochodzenia roszczeń odszkodowawczych od Skarbu Państwa - Tyska, Magdalena; Smoliński, Tomasz (Kortowski Przegląd Prawniczy, 2021)
The provisions of the civil procedure in the scope of a complaint for a declaration of non-compliance with the law of a final judgment present the institution of a complaint as one of the most formalized legal measures in the Polish civil law system. It is one of the institutions regulated among emergency measures. It should be assessed that the legislator very rigorously defined the grounds for bringing an action for a declaration of a declaration of a number of limitations. Complaint construction can be divided into certain stages. The multitude of elements of the complaint, as well as possible deficiencies that a party may commit in the complaint, unequivocally presupposes the conclusion that the complaint is one of the most difficult, if not the most difficult, means of appeal to edit. The legislator specified strict consequences in the event of failure to fulfill any of the obligatory elements of the complaint. Moreover, despite the rigorous nature of the regulations themselves, the judicature, including the Supreme Court, also requires extreme caution when formulating the complaint. A properly formulated complaint must meet not only purely formal requirements, but also very difficult to edit juridical arguments. In order to avoid possible mistakes, in this case also the obligatory attorney-at-law has been introduced. This compulsion applies only to the means of appeal, which precisely due to their complexity, require a detailed knowledge of the meanders of both procedural and substantive law. Therefore, despite the right introduction of certain restrictions by the legislator when drafting and submitting a complaint, it should be concluded that in some cases regulations aimed at helping a party only limit their freedom in ultimately making procedural decisions in their case, which should be considered unjustified.